KUALITAS BRIKET ARANG DARI KULIT SABUT BUAH NIPAH (Nypa fruticans WURMB) DALAM MENGHASILKAN ENERGI The qualty of charcoal briquettes that made from nypah (nypa fruticans wurmb) outshel to product energy - Rosidah Muis Radam; Lusyiani Lusyiani; Diana Ulfah; Noor Mirad Sari; Violet Violet (Jurnal Hutan Tropis, 2018)
The availability skin fiber of fruit Nipah abundant each season can be used as alternative energy sources such. The purpose of this study is to determine the quality of charcoal briquettes from the skin fiber of nipah peel in its ability to produce energy. The results of this study can be used as a consideration in the development of the utilization of the nipah plant part of the fruit peel as briquette fuel. The method used is to compare the capability of 1 kg of charcoal briquettes compared to the 1 liter kerosene capability inserted in the Hock stove with 16 axis in producing energy. The test do the Laboratory of Standardization Center for Industry of Banjarbaru. The Charcoal briquettes in this study contain 5.12% water content, ash content 4.15%, airborne content 36.66%, carbon content bound 58.19% and calorific value 5438,80 cal / gram. The results of charcoal briquette quality analysis when compared with SNI-01-6235-2000 charcoal quality standards of water content, ash content, and calorific values that meet the charcoal quality standard requirements as good fuel, but the content of fly and carbon bound does not meet the requirements charcoal quality standard, airborne content of 33.66% and carbon bound to 58.19%, according to SNI-01-6235-2000 maximum airborne content 15%. and carbon bound ≥ ≥ 77%. Average initial time of ignition for 3’25 “long smoldering 1 hour 9 ‘. The average time of boiling 1 liter of water is 22 ‘05 “. When compared to the use of kerosene by using the Hock stove with 16 axis and if converted to economic value, the charcoal briquettes results of this study can be used as a renewable energy alternative.Keywords: charcoal briquettes, skin fiber of fruit Nipah, energyKetersediaan kulit sabut buah Nipah yang melimpah setiap musimnya dapat dimanfaatkan menjadi sumber energy alternative. Tujuan yang ingin dicapai adalah untuk mengetahui kualitas briket arang kulit sabut buah nipah dalam kemampuannya menghasilkan energy. Manfaat penelitian ini sebagai bahan infotmasi untuk mengembangkan teknologi pengolahan bagian tumbuhan nipah yaitu bagian kulit buah sebagai bahan bakar briket. Metode yang digunakan adalah membandingkan kemampuan 1 kg briket arang dibandingkan dengan kemampuan 1 liter minyak tanah yang dimasukkan dalam kompor Hock sumbu 16 dalam mengthasilkan energy. Pengujian dilakukan di Laboratorium Balai Risert Standardisasi Industri Banjarbaru. Briket Arang dalam penelitian ini mengandung kadar air 5,12 %, kadar abu 4,15 % , kadar zat terbang 36,66 % , kadar carbon terikat 58,19 % dan nilai kalor 5438,80 cal/gram. Hasil pengujian sifat Fisik dan Kimia briket arang dibandingkan dengan SNI-01-6235-2000, parameter kadar air, kadar abu, dan nilai kalor yang memenuhi persyaratan standar kualitas arang sebagai bahan bakar yang baik, namun kadar zat terbang dan karbon terikat tidak memenuhi 3’25” lama membara 1 jam 9’. Rata-rata waktu mendidihkan 1 liter air adalah 22’ 05”. Jika dibandingkan dengan pemakaian minyak tanah dengan memakai kompor Hock 16 sumbu dan jika dikonversi ke nilai ekonomi, maka briket arang hasil penelitian ini dapat dijadikan sebagai energy alternative yang bersifat renewableKata kunci: Briket arang, kulit sabut buah nipah, energy